Rancang Bangun Sistem Filterisasi untuk Monitoring Kualitas Air Minum Rumah Tangga - Usita Putri Dwi Arindita (Politeknik Negeri Malang, 2019)
Processing water products sources into ready-to-drink water have been widely circulated in community, one of it's a household drinking water filter with 4 filter stages. Drinking water itself is indispensable for human body. It's because most of the human body is made up of water. To meet the water needs in human body, drinking water is required. Drinking water that consumed by community must meet drinking water standards that have been determined by Minister of Health Decree No. 492/2010, which must meet physical, chemical, biological and radioactive requirements.This research aimed at monitoring several drinking water quality parameters in form of Ph (6.5 - 8.5), Turbidity (<5 NTU) and temperature (22 ? - 27 ?) by using pH sensor, turbidity sensor and temperature sensor, and ON/OFF scheduling of ultraviolet light as an inhibitor of bacterial growth which then monitoring results will be sent via nodeMCU ESP8266 and displayed on WEB. The results of the Ph sensor readings show a reading accuracy of up to 97.28%, on the temperature sensor the reading accuracy reaches 98.7%, while the turbidity sensor has an accuracy level of up to 98.875%, the ON/OFF of UV light goes according to schedule. The application software used able to read and store data in real time from water quality sensor so users can monitor quality of drinking water. Water from filtration of water filter can be categorized as suitable for drinking in accordance with drinking water standard in the Decree of Minister of Health No. 492 in 2010.